Characterizing and Exploring the Implications of Maritime Irregular Warfare - Dunigan, Molly (RAND Corporation, 2012)
Although irregular warfare includes a range of activities in which naval forces have played an integral role, there has been little examination of the characteristics or potential of such operations in maritime environments. An assessment of the maritime component of a series of historical and ongoing operations reveals that current notions of irregular warfare would benefit from increased recognition of potential maritime contributions.